Literature-based learning in deradicalization education: An analysis of the novel “Api Jihad di Tanah Suriah” - Ilma, Labibah Sayaka; Soraya, Irma (Tawazun: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of Literature Based Learning in deradicalization education through the use of the novel Api Jihad di Tanah Suriah, a work based on the true story of a young man’s ideological journey that led him into radical beliefs, in the Aqidah Akhlak subject at MA Darun Najah Tulangan Sidoarjo. Employing a qualitative case study approach, this research explores the dynamics of the learning process, students’ responses, and the effectiveness of the novel as a medium for critical literacy in cultivating the values of religious moderation. The analysis was conducted through classroom observations and in-depth interviews. The findings indicate that Literature Based Learning fosters a more contextual, reflective, and relevant learning process concerning issues of radicalism among adolescents. The narrative and character development within the novel serve as catalysts for moral discussions, a proper understanding of the concept of jihad, and the internalization of humanitarian and national values. The implementation of Literature Based Learning is strengthened by three theoretical frameworks, Transformative Learning, Narrative Theory, and the Transactional Theory of Reading, which elucidate shifts in students’ perspectives, meaning-making through storytelling, and active interaction between readers and the text. This study affirms that literary works based on true events can serve as a strategic medium in school based deradicalization education. Abstrak Penelitian ini bertujuan menganalisis implementasi Literature Based Learning (LBL) dalam pendidikan deradikalisasi melalui pemanfaatan novel Api Jihad di Tanah Suriah, sebuah karya yang diangkat dari kisah nyata perjalanan ideologis seorang pemuda yang terjerumus dalam paham radikal, pada mata pelajaran Akidah Akhlak di MA Darun Najah Tulangan Sidoarjo. Menggunakan pendekatan kualitatif jenis studi kasus, penelitian ini menggali dinamika pembelajaran, respons siswa, serta efektivitas novel sebagai media literasi kritis dalam menanamkan nilai moderasi beragama. Analisis dilakukan melalui observasi kelas, serta wawancara mendalam. Hasil penelitian menunjukkan bahwa LBL mampu menghadirkan proses belajar yang lebih kontekstual, reflektif, dan relevan dengan isu radikalisme di kalangan remaja. Narasi tokoh dalam novel menjadi pemicu diskusi moral, pemahaman konsep jihad yang benar, serta internalisasi nilai kemanusiaan dan kebangsaan. Penerapan LBL diperkuat melalui tiga kerangka teori, Transformative Learning, Narrative Theory, dan Transactional Theory of Reading, yang menjelaskan perubahan perspektif siswa, konstruksi makna melalui cerita, serta interaksi aktif antara pembaca dan teks. Penelitian ini menegaskan bahwa karya sastra berbasis kisah nyata dapat menjadi sarana strategis dalam pendidikan deradikalisasi di sekolah.